New developments in Sjogren's syndrome. (24th December 2021) - Thalayasingam, Nishanthi; Baldwin, Kelly; Judd, Claire; Ng, Wan-Fai
Abstract: SS is a chronic, autoimmune condition characterized by lymphocytic infiltration of the exocrine glands and B-cell dysfunction. Current treatment strategies are largely empirical and offer only symptomatic relief for patients. There are no proven treatments that alter disease progression or treat the systemic manifestations of disease. B-cell depletion is used in patients with systemic disease but its overall clinical efficacy has not been demonstrated in two large randomized controlled trials. Studies are now focussing on alternative strategies to target B-cells, including co-stimulation targets, with promising data. It is increasingly clear that clinical trials in SS will require patient stratification and relevant and sensitive outcome measures to identify successful treatment modalities.